A Case of Drastic Reduction of Membranous Substances in the Pharynx by Interprofessional Cooperative Oral Care - Masahiko Okubo; Hideyuki Kamimura; Tsuyoshi Sato; Shoichiro Kokabu (Case Reports in Dentistry)
Membranous substances in the pharynx are occasionally observed in tube feeding patients during the fiberoptic endoscopic evaluation of swallowing. Although the mechanism of the formation of these deposits sometimes causes problems, such as dysphagia, asphyxia, or aspiration pneumonia, a 91-year-old male complained about difficulty of swallowing. He had a history of cerebral infarction and aspiration pneumonitis. There was a large amount of oral desquamated epithelium, dental plaque, and calculus in his mouth. Nurses and care workers administered oral care such as rubbing the tongue and buccal mucosa daily. Dentists and oral hygienists visited and provided special oral care three times per week. At least for 77 days, the patient had no recurrence of pneumonitis. The oral desquamated epithelium and membranous substances in the pharynx decreased drastically. 2 months after the first examination, the patient was able to start rehabilitation with food. Some studies have indicated that pharyngeal deposits are derived from the oral mucosa, and through our case, we realized the importance of daily oral care by interprofessional work to reduce membranous substances in the pharynx.